Ancient graphite in the Eoarchean quartz–pyroxene rocks from Akilia in southern West Greenland I: Petrographic and spectroscopic characterization - Papineau, Dominic; De Gregorio, Bradley T.; Cody, George D.; Fries, Marc D.; Mojzsis, Stephen J.; Steele, Andrew; Stroud, Rhonda M.; Fogel, Marilyn L. (Geochimica et cosmochimica acta, 2010)
Because all known Eoarchean (>3.65 Ga) volcano-sedimentary terranes are locked in granitoid gneiss complexes that have experienced high degrees of metamorphism and deformation, the origin and mode of preservation of carbonaceous material in the oldest metasedimentary rocks remain a subject of vigorous debate. To determine the biogenicity of carbon in graphite in such rocks, carbonaceous material must be demonstrably indigenous and its composition should be consistent with thermally altered biogenic carbon as well as inconsistent with abiogenic carbon. Here we report the petrological and spectroscopic characteristics of carbonaceous material, typically associated with individual apatite grains, but also with various other minerals including calcite, in a >3.83 Ga granulite-facies ferruginous quartz-pyroxene unit (Qp rock) from the island of Akilia in southern West Greenland. In thin sections of the fine-grained parts of Akilia Qp rock sample G91-26, mapped apatites were found to be associated with graphite in about 20% of the occurrences. Raman spectra of this carbonaceous material had strong G-band and small D-band absorptions indicative of crystalline graphite. Three apatite-associated graphites were found to contain curled graphite structures, identified by an anomalously intense second-order D-band (or 2D-band) Raman mode. These structures are similar to graphite whiskers or cones documented to form at high temperatures. Raman spectra of apatite-associated graphite were consistent with formation at temperatures calculated to be between 635 and 830 °C, which are consistent with granulite-facies metamorphic conditions. Three graphite targets extracted by focused ion beam (FIB) methods contained thin graphite coatings on apatite grains rather than inclusions sensu stricto as inferred from transmitted light microscopy and Raman spectroscopy. TEM analyses of graphite in these FIB sections showed a (0 0 0 2) interplanar spacing between 3.41 and 3.64 Å for apatite-associated graphite, which is larger than the spacing of pure graphite (3.35 Å) and may be caused by the presence of non-carbon heteroatoms in interlayer sites. Samples analyzed by synchrotron-based scanning transmission X-ray microscopy (STXM) also confirmed the presence of crystalline graphite, but abundances of N and O heteroatoms were below detection limit for this method. Graphite in the Akilia Qp rock was also found to occur in complex polyphase mineral assemblages of hornblende ± calcite ± sulfides ± magnetite that point to high-temperature precipitation from carbon-bearing fluids. These complex mineral assemblages may represent another generation of graphitization that could have occurred during the amphibolite-facies metamorphic event at 2.7 Ga. Several observations point to graphitization from high-temperature fluid-deposition for some of the Akilia graphite and our results do not exclude a biogenic source of carbon in graphite associated with apatite, but ambiguities remain for the origin of this carbon.